2022
DOI: 10.13057/biodiv/d231016
|View full text |Cite
|
Sign up to set email alerts
|

Biomass accumulation and carbon sequestration potential in varying tree species, ages and densities in Gunung Bromo Education Forest, Central Java, Indonesia

Abstract: Abstract. Darmawan AA, Ariyanto DP, Basuki TM, Syamsiyah J, Dewi WS. 2022. Biomass accumulation and carbon sequestration potential in varying tree species, ages and densities in Gunung Bromo Education Forest, Central Java, Indonesia. Biodiversitas 23: 5093-5100. Forest biomass plays an important role in carbon storage to mitigate climate change. While many studies have investigated the carbon stock of various forests, adding knowledge in the context of education forest might enrich the importance of this fores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 45 publications
2
9
0
1
Order By: Relevance
“…The soil indicator used to calculate the SQI is the Minimum Data Set (MDS) obtained from Principal Component Analysis (PCA) and Pearson correlation analysis. The soil quality index is obtained by multiplying the weight index (Wi) and score index (Si) based on Nusantara et al [35], which is shown in Equation (1). Weight index (Wi) is the result of dividing the proportion with the cumulative on the PCA analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The soil indicator used to calculate the SQI is the Minimum Data Set (MDS) obtained from Principal Component Analysis (PCA) and Pearson correlation analysis. The soil quality index is obtained by multiplying the weight index (Wi) and score index (Si) based on Nusantara et al [35], which is shown in Equation (1). Weight index (Wi) is the result of dividing the proportion with the cumulative on the PCA analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Located in Karanganyar Regency, Central Java Province, Indonesia, the Alas Bromo educational forest is strategically important to Universitas Sebelas Maret (UNS) for education, research, and the advancement of science and technology [1]. Like other tropical forests, the Alas Bromo Forest provides numerous environmental benefits and indirectly contributes to biodiversity conservation and climate regulation [2].…”
Section: Introductionmentioning
confidence: 99%
“…Berdasarkan tabel tersebut dapat dilihat bahwa permudaan pohon memiliki nilai serapan karbon dan biomassa yang lebih tinggi dibandingkan dengan permudaan pancang. Hal ini dikarenakan 84,9% kelas usia pohon berkontribusi terhadap biomassa karbon dimana biomassa akan semakin meningkat secara signifikan seiring dengan bertambahnya usia pohon yang ditandai dengan peningkatan ukuran diameter batang (Darmawan et al, 2022). Keterkaitan antara aspek kelas usia pohon dengan peningkatan produksi biomassa dapat dilihat pada tabel dimana Taman Monumen 45 memiliki produksi biomassa yang lebih tinggi dibandingkan dengan Taman Jaya Wijaya hal ini dikarenakan rata-rata diameter pohon yang ada di Taman Monumen 45 lebih besar daripada diameter pohon yang ada di Taman Jaya Wijaya dengan selisih ratarata sebesar 2.8 cm.…”
Section: Biodiversitas Vegetasiunclassified

Untitled

Hikari,
Syahrani,
Luthfia
et al. 2024
JRS
“…The aforementioned numerical values indicate the soil's ability to store carbon, which is a critical determinant in reducing atmospheric carbon dioxide concentrations. The historical influence of land management practices such as fertilization at the research location, which incidentally is former agroforestry land, is thought to support high soil carbon uptake [27,28] The soil carbon sequestration method involves utilizing soils as substantial repositories for the retention of organic carbon, hence assuming a pivotal function in the amelioration of carbon emissions. The results emphasize the importance of conserving and improving soil organic carbon levels, as it plays a critical role in raising soil fertility and increasing the capacity for carbon sequestration.…”
Section: Carbon Stored In Soilmentioning
confidence: 99%